Model Experiential Learning dalam Menumbuhkan Kemampuan High Order Thinking Skills (HOTS) - Fadliyah, Laily Safarina; Fanani, Achmad (Jurnal Pendidikan Dasar, 2024)
This research aimed to 1) describe the implementation of the experiential learning model in cultivating High Order Thinking Skills (HOTS); 2) determine students' activities in the application of the experiential learning model in foster High Order Thinking Skills (HOTS); 3) assess students' responses to learning using the experiential learning model; 4) evaluate students' learning outcomes with the experiential learning model in developing High Order Thinking Skills (HOTS). This study adopted a descriptive quantitative research design. This study is a type of descriptive quantitative research. The research subjects are grade VA students at SDN Dukuh Menanggal I/424 Surabaya. Data collection techniques use instruments such as observation sheets, questionnaires, and tests. Based on the research results, the experiential learning model can be implemented effectively and successfully enhances students' HOTS. Students' activities during the learning process reach a score of 90, in accordance with the HOTS activity indicators. Students' responses to the implementation of the experiential learning model are very positive. Overall, the learning outcomes achieve a mastery level of 95% with the category "Very Good."